(untitled) (Journal of the College of Basic Education, 2022)
Modern age aspects and its related consequences forms such as global competition, saturated markets and the developed info tech, all contribute to raising clients’ sense awareness and created an unguaranteed long-term success situation, which cannot be fulfilled only by price reduction, increase the type and the numbers of the employees, or even providing after sale services, but expands beyond that to sustaining a long-term relationship between the company and the client, in what we name as (Loyalty) in this research. Thus this crucial modern design element makes all companies and design firms strive to comprehend its entire consents, in order to avoid the competitors’ products affects on the one hand, and invest the gained pre-studies approved (Loyalty Values) aspects. Which has a major role in raising earnings, reducing the cost price, proven learning from previous mistakes and many other more points on the other hand. The trademark existence in the market becomes a challenge that deeply associated with the loyalty factor as it likely described as a survival’s struggle. Many specialized types of research have been run on this matter, which varies on their targets from academic analytic studies to a study that strived to improve the importance of the Loyalty factor and how to reach its achievements tools. However, we did not find any design-oriented study in which deals with this factor in terms of design, all were produced to serve the marketing, statistical and financial perspectives only. Thus the need of this research becomes important and emerges quite an important question as well: what is the role of the products’ design in supporting the clients’ loyalty values, how can designers include loyalty factor in his design and strive to fulfill all of its sides from a design vision. The researcher used many specialized studies and cultural-related literature as well in order to answer that question Which resulted in a set of indicators used by the researcher in the building of the analysis form and the application of its paragraphs on the sample of the research, which included the designs of electronic products for Apple Inc. and its latest products for 2018. Resulting in a set of findings and conclusion and figure out the research goals which is identifying the designer’s role during the production process, those are concluded to be so active in strengthening the clients’ loyalty values which are elaborated on the research’s content.